The use of polymeric meshes for pelvic organ prolapse: Current concepts, challenges, and future perspectives. Issue 3 (20th June 2019) - Mancuso, Elena; Downey, Candice; Doxford‐Hook, Elizabeth; Bryant, Michael G; Culmer, Peter
Abstract: Pelvic organ prolapse (POP) is one of the most common chronic disorders in women, impacting the quality of life of millions of them worldwide. More than 100 surgical procedures have been developed over the decades to treat POP. However, the failure of conservative strategies and the number of patients with recurrence risk have increased the need for further adjuvant treatments. Since their introduction, surgical synthetic meshes have dramatically transformed POP repair showing superior anatomic outcomes in comparison to traditional approaches. Although significant progress has been attained, among the meshes in clinical use, there is no single mesh appropriate for every surgery. Furthermore, due to the risk of complications including acute and chronic infection, mesh shrinkage, and erosion of the tissue, the benefits of the use of meshes have recently been questioned. The aim of this work is to review the evolution of POP surgery, analyzing the current challenges, and detailing the key factors pertinent to the design of new mesh systems. Starting with a description of the pelvic floor anatomy, the article then presents the traditional treatments used in pelvic organ disorders. Next, the development of synthetic meshes is described with an insight into how their function is dependent on both mesh design variables (i.e., material, structure, and functional treatment) and surgical applications. These are then linked to common mesh‐related complications, and an indication of current research aiming to address these issues.